Embryogenic Callus Induction and Efficient Plant Regeneration in Three Varieties of Soybean (Glycine max) (Plant Tissue Culture and Biotechnology, 2017)
An efficient callus induction and plant regeneration system has been developed using three local soybean (Glycine max L.) varieties. All the varieties showed good callusing (78.30 ‐ 88.80%) from shoot tip (ST) in MS + 3.0 mg/l 2,4‐D + 1.0 mg/l BAP. Best callus induction and embryo formation were recorded in T5 for BS‐6 as 88.80 and 81.20%, respectively from ST. In case of cotyledonary node (CN) the maximum callus induction (82.40%) and embryo formation (74.20%) were recorded also in T5 for BS‐6. Highest frequency (79.40%) of plant regeneration was recorded where ST were used and cultured in MS supplemented with 2.5 mg/l BAP + 1.0 mg/l NAA as well as 76.30% from CN in BS‐6. The length of shoot was observed 5.32 and 4.62 cm, respectively from ST and CN for BS‐6 with the same medium composition. It was observed that half strength of MS + 2.0 mg/l IBA showed best rooting (9.04). Among the genotypes BS‐6 proved to be best explants than ST that exhibited better performance on callus induction and green plant regeneration for all parameters.Plant Tissue Cult. & Biotech. 27(1): 41-50, 2017 (June)